The influence of music tempo on consumer behavior at grocery stores - Septyowati, Inna; Prabaswari, Atyanti Dyah; Sari, Amarria Dila; Purnomo, Hari; Irawan, Ade (OPSI, 2024)
Music is the art of sound arranged in such a way as to produce beautiful rhythms, melodies and harmonies. Music itself has been widely used as background sound in various fields, one of which is the retail business. This research aims to see the influence of the type of music tempo on consumer purchasing behavior where there are two types of tempos used, fast music tempo and slow music tempo. The method used to see the effect of music tempo on consumer purchasing behavior is the multiple linear regression statistical test. For fast music tempo types there will be 5 questions, 5 questions for slow music tempo types, and 3 questions for consumer purchasing behavior. The population used in this research includes consumers from five grocery stores located in the Yogyakarta Province, Indonesia, who have carried out shopping activities at these stores in May 2023, with a sample size of 32 respondents. The analysis technique used is descriptive analysis and multiple linear regression analysis. The results of this regression analysis show that there is a positive influence of slow music tempo on consumer purchasing behavior, while fast tempo music has negative influence on consumer purchasing behavior.